Record of Ragnarok. Volume 9 - Umemura, Shin'ya; Fukui, Takumi (Viz signature., 2024)
"Once every millennium, the gods assemble to decide if humanity is worthy of its continued existence or if it should be destroyed! When the verdict is destruction, the final battle between the gods and mortal heroes will decide the survival or extinction of the human race--a battle known as Ragnarok! In the Valhalla arena, Raiden Tameemon stands ready to fight for humanity after unleashing his superhuman muscles. Representing the gods, Shiva the Destroyer is confident of his eventual victory. As the two are squaring off, Loki follows a hunch, seeking the secret of Volund, the power the Valkyries use to merge with the human heroes' weapons. What he finds is an insolent Buddha who might know something about it. But getting the answer might require an unsanctioned brawl between two rowdy groups of gods and human heroes!"--